Filasafat Ilmu dalam Kajian Ilmu Hadis: Telaah Tentang Epistemologi, Ontologi, dan Aksiologi - Muhammad Fadzli; Albarra Gilang Andika; Siti Sarah Muhamad; Andi Rosa (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
The study of philosophy of science in the context of hadith science through epistemology, ontology, and axiology approaches. Hadith as the second source of Islamic teachings after the Qur'an has an important role in shaping the law, ethics, and culture of Muslims. Using the literature study method, this article explores how philosophy of science can be used to understand the basis of knowledge (epistemology), the essence of the existence of hadith (ontology), and the value and benefits of its application in life (axiology). This research finds that the philosophy of science approach helps to strengthen the validity, depth, and relevance of hadith studies in the contemporary era, while affirming the importance of Islamic values in the development of science. Thus, this article contributes to the integration between philosophy and Islamic studies in enriching the rational and scientific understanding of hadith.